Предмет: Алгебра,
автор: Машка08
Решить уравнение.
(x-2)^4-4(x-2)^2-5=0
Ответы
Автор ответа:
0
(x-2)⁴-4(x-2)²-5=0
Выполним замену (х-2)²=у, тогда (х-2)⁴=у²
у²-4у-5=0
D=4²+4*5=36
y₁=(4-6)/2=1
y₂=(4+6)/2=5
1) y₁=1
(x-2)²=1
x-2=1
x₁=3
x-2=-1
x₂=1
2) y₂=5
(x-2)²=5
x-2=√5
x₃=2+√5
x-2=-√5
x₄=2-√5
Ответ 2-√5; 1; 3; 2+√5
Выполним замену (х-2)²=у, тогда (х-2)⁴=у²
у²-4у-5=0
D=4²+4*5=36
y₁=(4-6)/2=1
y₂=(4+6)/2=5
1) y₁=1
(x-2)²=1
x-2=1
x₁=3
x-2=-1
x₂=1
2) y₂=5
(x-2)²=5
x-2=√5
x₃=2+√5
x-2=-√5
x₄=2-√5
Ответ 2-√5; 1; 3; 2+√5
Похожие вопросы
Предмет: Биология,
автор: ivanna2782
Предмет: Русский язык,
автор: pupirka95
Предмет: История,
автор: aenpppp
Предмет: Обществознание,
автор: Аноним
Предмет: Математика,
автор: danka99